Hydraulic fracking: a market forecast: Colombia - Mendoza Varela, Fabian (2016)
The oil and gas exploration and production industry normally has three major actors, the first one being the governments, who dictate the 'game' rules and provide the framework for attracting investors to this sector. The second one consists of operators, large companies and joint ventures between experienced operators and investment funds who are seeking attractive returns on investments, and the third actor is service companies who provide all services required to extract oil and gas from the subsurface and send them to refineries. The oil and gas service market moves according to international oil prices. High prices mean more exploration, which in turn mean more investment and opportunities for service companies. After more than five marvelous years of a boom in oil prices, a contraction is severely affecting the oil and gas industry. An option for international or multinational oil and gas service companies is to diversify their geographic areas of influence and expand their presence in countries where oil and gas investors are moving resources, especially in countries where oil and gas represent a significant percentage of its Gross Domestic Product (GDP) and government rules are more flexible, which increases the possibility to maximize returns. The purpose of this paper is to understand if it is possible to introduce a specific service from a Chinese oil and gas service company in Colombia under the current economic situation: hydraulic fracturing services for unconventional resources. By using data from previous studies that estimate the unconventional resources potential in Colombia, current and potential customers, service and price benchmarking, some market positioning strategies as well a risk mitigation plan that could reduce exposure, it will be possible to ascertain whether it applies to this new service or not, and if possible, to determine what barriers could this company face to obtain its goal.